Pengelolaan Stok Lemari Kaca dengan Sistem SCM Berbasis Web untuk Efisiensi Produksi - Apriliani; Rahmadani, Nurul; Suparmadi (Institut Teknologi Garut, 2025)
Utama Aluminium is a business engaged in the sale of glass cabinets. The problem faced in the operational activities of this business is irregularity in the management of raw material supplies. This condition is caused by inconsistency in supply from suppliers, which results in stock shortages and delays in orders, and on the other hand, there have also been instances of excess raw materials. The purpose of this study is to design a raw material inventory management application system for the glass cabinet production process, in order to optimize the management of raw material inventory, which has been a challenge in production activities at Utama Aluminium. The method used in this study is a descriptive qualitative method, with a case study approach at the company concerned. The results of implementing a web-based supply chain management (SCM) system showed a significant increase in efficiency: process time decreased by up to 40% through system automation and integration, operational costs were reduced by up to 25% due to labor efficiency and a decrease in error rates, stock accuracy increased to 95% with supplies matching demand, lead time was reduced by an average of 2 days, and the number of product returns decreased by up to 30% thanks to more accurate data information. This research can help the MSME sector improve distribution efficiency and inventory accuracy.